IDENTIFIKASI DAN PERBAIKAN JARINGAN IRIGASI COLO TIMUR KABUPATEN SUKOHARJO (STUDI KASUS: SALURAN SEKUNDER AMBIL-AMBIL) - Sukma Wijaya; Gunarso Gunarso; Teguh Yuono; Paska Wijayanti (Journal of Civil Engineering and Infrastructure Technology, 2023)
A good irrigation building should be able to function optimally by considering effectiveness level of water management, if irrigation building maintenance is not carried out routinely and periodically it will have an impact on the main function of irrigation networks. This study aims to obtain data and information, obtain solutions for efforts to repair the damage to the secondary canal in the East Colo Irrigation area in Sukoharjo, and determine the costs incurred for rehabilitation. The methods used in this study were observation, interviews, literature study, and written data collection in the field. The results of the study include the identification of damage to the Secondary Canal Ambi- ambil is classified into three, namely; Minor damage, including cleaning of vegetation around the canal and cracks in the canal. Moderate damage, including painting of sluice gates and replacement of wooden valve plates with steel valve plates. Serious damage, including sedimentation and damage to canals. Efforts to repair or deal with damage to the Secondary Canal Ambil-ambil, namely: Cleaning of vegetation around the Secondary Canal Ambil- ambil, painting of 8 water gates on the Secondary Canal Ambil-ambil, replacing the sluice plate on B.Am 5 Secondary Canal Ambil- ambil, Silting by Sedimentation of Canal Sedimentation on B.Am 4 (1303 m to 2041 m), Handling of heavy damage, Replacement of walls and floors with U-gutter on Secondary Canal Ambil-ambil B.Am 4 (1 m to 764 m). And the budget plan for the repair of the Secondary Canal Ambil- ambil is 1.501.832.684,00